Mental health presentations to the emergency department: A perspective on the involvement of social support networks. (September 2019) - Marynowski-Traczyk, Donna; Broadbent, Marc; Kinner, Stuart A.; FitzGerald, Gerard; Heffernan, Ed; Johnston, Amy; Young, Jesse T.; Keijzers, Gerben; Scuffham, Paul; Bosley, Emma; Martin-Khan, Melinda; Zhang, Ping; et al.
Abstract: The involvement of families, carers and significant others (i.e. social support networks) has a positive corollary for a person experiencing mental health problems. Accordingly, in Australia involvement of social support networks within mental health services is endorsed in national health policy and service guidelines. Despite the endorsement, this is yet to be fully realised in all areas that provide mental health services, including emergency departments. Social support networks are integral in the provision of mental health consumers' care. Supporting the involvement of social support networks in the emergency department can provide healthcare services with opportunities for enhanced and cost-effective care, contributing to improved outcomes for consumers. An overview of some of the barriers and facilitators of social support network involvement is provided. The intention of this paper is to encourage reflection and dialogue on this important area of mental health service provision and support the evolution of a new paradigm of research into social support network involvement in the emergency department.